Grapevine Root Distribution and Density in Deep Soil Layers Under Different Soil Management Practices - Vania Lanari; Luca Pallotti; Tania Lattanzi; Oriana Silvestroni (Plants)
Grapevine root distribution and density influence mineral and water absorption and are affected by soil management and the use of cover crops. This study, conducted in a ten-year-old commercial Mediterranean vineyard with desiccant-managed inter-rows, compares the effects of three different soil management practices—minimum tillage (MT), spontaneous natural covering (NC), and a commercial grass mixture (GM)—on root development in Montepulciano vines grafted onto Kober 5BB rootstocks. Root length, diameter, and weight across different soil layers were analyzed by digging trenches. The results show that thin roots, primarily responsible for water and nutrient absorption, ensure greater soil volume exploration, while medium-to-large roots contribute mainly to root biomass. The presence of cover crops reduces root development in the upper soil layers due to competition with herbaceous species; however, this promotes deeper root exploration and increases the total root length per plant. In the deeper soil layers, root growth is limited by higher soil compaction. Tillage enhances the development of medium-to-large roots and increases the total root biomass per plant. In conclusion, soil management influences vine root development, and competition from cover crops stimulates the growth of absorbing roots in deeper soil layers.